Methods Of Improving Simultaneous Translation - Yusupova Nargiza Abdulhafizovna (Genius Journals, 2022)
This article provides information on how to improve simultaneous translation.Information about listener and simultaneous interpreter capabilities is provided.
Keywords: Simultaneous Interpreter; Listener; Speaker; English